Link Between the Conduct as Strategies and Training of Business - G., José; Vargas-Hernández (International Journal For Research In Business, Management And Accounting, 2015)
Industrial systems have received attention in recent years to explain the behavior ofcompanies from a broad perspective, integrating business strategy with structure.Collaborative network is a model that explains the structure of industrial systems to analyzeinteractions through methods that combine economic with social elements. This paperdiscusses how partnership strategies of firms derived from external forces to theorganization, and implemented by behaviors, shapes the structure, identity and governanceof local business networks around a common goal, and highlights the role of agents in thebusiness process evolution of the formalization of networks.